Peculiarities of performing a throw uchi-mata under the conditions of a competitive battle - Levitsky, A.G.; Matveyev, D. A.; Potsipun, A. A.; Oshina, O. V. - (Theory and Practice of Physical Culture, 2022)
Objective of the study was to conduct a biomechanical analysis of the throw Uchi-Mata in conditions of high-level competitions. Methods and structure of the study. To analyze the throw, a video was taken from the Internet, containing fragments of the fights of the Olympic champion in judo Toshihiko Koga. Next, the model was determined, due to which the throw was performed. Results and conclusions. In the course of the analysis of the throw Uchi-Mata, the authors calculate the speed of the center of gravity modulo for both athletes, the changes in the speed of the center of gravity modulo, as well as the projections of these values on the coordinate axes. Based on the intervals of the values ??of the velocities of the centers of gravity, the projections of the velocities, it is concluded that in the process of preparing and performing the throw, the opponent accelerates in the horizontal plane. The trajectory of the center of gravity of the attacked athlete indicates his preliminary swinging in the vertical plane before the throw. The results of the study can be used in the wrestling training process at the stage of sports specialization.